Analisis Service Quality dan Penggunaan BRI Mobile terhadap Loyalitas Nasabah di BRI Kantor Cabang Blitar - Setyoadi Pambudi; Samlatul Izzah; Rizky Aida Fitri (Jurnal Simki Economic, 2025)
This research process aims to determine how strong the influence of service quality on customer loyalty of Bank BRI KC Blitar. The impact of using BRI Mobile on customer loyalty at BRI KC Blitar. How strong is the influence of service quality and the use of mobile banking on customer loyalty of BRI KC Blitar. The research approach uses quantitative research, for data analysis cross-sectional data and multiple linear regression analysis models are used to calculate the results of the questionnaire using a Likert scale. Based on the results of data analysis conducted by the researcher, it can be concluded that service quality has a positive and significant effect on customer loyalty. When viewed from the value of the importance of the service quality variable, the t table is 0.000 <0.05, namely 3.684> 1.65, then Ho is rejected and H1 is accepted. The use of mobile banking has a positive and significant effect on customer loyalty. It can be measured by the significance value of the satisfaction variable of 0.009 t table or 2.640 (1%) <1.65. H0 is rejected and H2 is accepted. Service quality and the use of BRI Mobile have a positive and significant effect simultaneously on customer loyalty. Judging from the significance value of 0.000 <0.05 and obtained the calculated F value> F table which is 13.210> 3.05. This indicates that H0 is rejected and H3 is accepted.